Large-scale experimental investigation of biotreated sand column using different grouting pipe configurations - Chunyan Wang; Zhikang Wei; Jinquan Shi; Xiang He (PLoS ONE, 2026)
Microbially induced carbonate precipitation (MICP) has considerable potential for applications such as soil improvement, erosion control, and heavy metal remediation. However, the extent to which grouting pipe configuration affects treatment performance remains unclear. To address this gap, this study investigated the effects of grouting pipe configuration on the reinforcement behaviour of large-scale biotreated sand columns. Large-scale model tests were conducted using conventional vertical pipes and a newly proposed spiral pipe under different grouting procedures. Calcium carbonate content, unconfined compressive strength, penetration resistance, and microscopic characteristics were analysed to evaluate reinforcement range, spatial uniformity, and treatment depth. The results show that pipe configuration plays a key role in controlling calcium carbonate distribution and reinforcement performance. The one-pipe-injection-extraction configuration produced a limited effective reinforcement radius of about 0.09 m, whereas both the three-injection-one-extraction and spiral-injection-one-extraction configurations increased this value to about 0.15 m. Compared with conventional vertical pipes, the spiral configuration produced a more uniform distribution of calcium carbonate content and strength by reducing local enrichment and weakly treated zones. For the 1.5 m-high specimen, relatively uniform reinforcement was mainly achieved within the upper 0.6 m under the present pressure level. This study provides a practical pipe-layout strategy for improving the uniformity of field-scale MICP treatment and offers useful guidance for the design of bio-grouting systems.